MALT1 targeting suppresses CARD14‐induced psoriatic dermatitis in mice. (28th April 2020) - Van Nuffel, Elien; Staal, Jens; Baudelet, Griet; Haegman, Mira; Driege, Yasmine; Hochepied, Tino; Afonina, Inna S; Beyaert, Rudi
Abstract: CARD14 gain‐of‐function mutations cause psoriasis in humans and mice. Together with BCL10 and the protease MALT1, mutant CARD14 forms a signaling node that mediates increased NF‐κB signaling and proinflammatory gene expression in keratinocytes. However, it remains unclear whether psoriasis in response to CARD14 hyperactivation is keratinocyte‐intrinsic or requires CARD14 signaling in other cells. Moreover, the in vivo effect of MALT1 targeting on mutant CARD14‐induced psoriasis has not yet been documented. Here, we show that inducible keratinocyte‐specific expression of CARD14 E138A in mice rapidly induces epidermal thickening and inflammation as well as increased expression of several genes associated with psoriasis in humans. Keratinocyte‐specific MALT1 deletion as well as oral treatment of mice with a specific MALT1 protease inhibitor strongly reduces psoriatic skin disease in CARD14 E138A mice. Together, these data illustrate a keratinocyte‐intrinsic causal role of enhanced CARD14/MALT1 signaling in the pathogenesis of psoriasis and show the potential of MALT1 inhibition for the treatment of psoriasis. Synopsis: Expression of a pathogenic human CARD14 mutant transgene in keratinocytes is sufficient to drive psoriasis‐like dermatitis in mice, which can be inhibited by treatment with a MALT1 protease inhibitor. Keratinocyte‐specific expression of a human psoriasis‐associated CARD14 E138A mutant transgene in mice induces skin epidermal thickening and inflammation. CARD14 E138A expression in keratinocytes activates MALT1 proteolytic activity in murine skin. Oral treatment of mice with a MALT1 protease inhibitor reduces psoriatic dermatitis in CARD14 E138A expressing mice. Abstract : Expression of a pathogenic human CARD14 mutant transgene in keratinocytes is sufficient to drive psoriasis‐like dermatitis in mice, which can be inhibited by treatment with a MALT1 protease inhibitor.